2011
DOI: 10.1371/journal.pone.0017537
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of 63 MicroRNAs in the Asian Seabass Lates calcarifer

Abstract: BackgroundMicroRNAs (miRNAs) play an important role in the regulation of many fundamental biological processes. So far miRNAs have been only identified in a few fish species, although there are over 30,000 fish species living under different environmental conditions on the earth. Here, we described an approach to identify conserved miRNAs and characterized their expression patterns in different tissues for the first time in a food fish species Asian seabass (Lates calcarifer).Methodology/Principal FindingsBy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 78 publications
4
40
0
Order By: Relevance
“…2 and Dataset S2) is in agreement with reports showing pre-miRNA conservation in the two arms but allowing variation in the termini and the big loop regions [26], [27], [28]. Some of the identified precursors were similar to mammalian pre-miRNAs but have not been previously reported in teleosts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2 and Dataset S2) is in agreement with reports showing pre-miRNA conservation in the two arms but allowing variation in the termini and the big loop regions [26], [27], [28]. Some of the identified precursors were similar to mammalian pre-miRNAs but have not been previously reported in teleosts.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Il-1β is expressed in various organs; Il-12β is highly expressed in immune related organs; and Il-6 exhibits more limited expression pattern and is primarily detected in thymus and brain [40]. Vibrio harveyi challenge experiment in Asian seabass ( Lates calcarifer ) has shown rapid transient elevated expression of both Il-1β and miR-21 in three immune related organs, indicating role of miRNAs in acute inflammatory immune responses [28]. In mammals, miRNAs are reported to target cytokine transcripts [41], [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study on Nilaparvata lugens reported that miR-263a was found as high abundant miRNAs in the last instar female nymph females [78]. Both miR-8 and miR-184 were reported in the embryos of Drosophila [79, 80], mosquitoes [68, 81], silk worm [82], Schistosoma japonicum [83], zebrafish [84], Asian seabass[85], mouse [8688] and humans [15, 89]. This suggest a conservative developmental function for these two miRNAs across different animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a number of miRNA species was identified in Asian seabass ( Lates calcarifer ) eye (Xia et al 2011). Spatial localization of miRNAs revealed cell type- and developmental stage-specific expression patterns (Kapsimali et al 2007).…”
Section: Mirna In Teleost Developmentmentioning
confidence: 99%